INTEGRASI NILAI-NILAI MODERASI BERAGAMA DALAM KURIKULUM PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH - Sumianti Sumianti; Bayu Mujrimin; Supriadi Supriadi (Universitas Islam Negeri Sumatera Utara Medan, 2025)
The rise of intolerance and radicalism among adolescents has become a serious challenge in the field of education, particularly in Islamic Religious Education (PAI). This study aims to examine the extent to which the values of religious moderation such as tolerance, anti-radicalism, and patriotism are integrated into the PAI curriculum at the secondary school level. This research employs a descriptive qualitative approach through content analysis of curriculum documents, including Core Competencies (KI), Basic Competencies (KD), syllabi, and PAI textbooks. The findings reveal that the values of religious moderation are reflected in several learning materials, especially on topics such as ethics toward others, interfaith harmony, and the role of religion in national life. However, the implementation of these values in the classroom still faces obstacles, such as limited teacher understanding and a tendency toward normative teaching methods. Therefore, strengthening the curriculum and enhancing teacher competence in delivering moderation values are urgently needed to ensure that PAI effectively contributes to shaping a generation of moderate, tolerant, and patriotic Muslims.